The Protective Effect of a Short Peptide Derived from Cold-inducible RNA-binding Protein in Renal Ischemia-Reperfusion Injury - McGinn, Joseph (Shock, 2018)
Extracellular cold-inducible RNA-binding protein (CIRP) functions as damage-associated molecular pattern (DAMP) and has been demonstrated to be responsible in part for the damage occurring after renal ischemia-reperfusion (I/R). A short peptide derived from CIRP, named C23, binds to myeloid differentiation factor 2 (MD2), a Toll-like receptor 4 (TLR4) co-receptor. We hypothesize that C23 reduces renal ischemia-reperfusion (RIR) injury by blocking CIRP. We observed that pre-treatment with C23 significantly decreased the levels of recombinant mouse CIRP-induced TNF-α in a dose-dependent fashion in cultured macrophages. C57BL/6 mice were subjected to bilateral renal pedicle clamps for 35 min to induce ischemia, followed by reperfusion for 24 h and harvest of blood and renal tissue. C23 peptide (8 mg/kg) or vehicle was injected intraperitoneally at the beginning of reperfusion. Plasma TNF-α, IL-1β, and IL-6 levels were decreased in C23-treated RIR mice as compared to vehicle-treated mice by 74%, 85% and 68%, respectively. Expressions of TNF-α and keratinocyte chemoattractant (KC) in the kidneys from C23-treated mice was decreased by 55% and 60%, respectively. Expression of kidney injury molecule-1 (KIM-1) and neutrophil gelatinase-associated lipocalin (NGAL) in the kidney of C23-treated mice were significantly reduced by 46% and 55%, respectively. Renal tissue histological assessments revealed significant reduction in damage score by 44% in C23-treated mice. Finally, a survival study revealed a significant survival advantage with a 70% survival rate in C23 group versus 37 % in vehicle group. Thus, C23 has potential as a novel therapy for the patients suffering from I/R-induced renal injury.